Os advérbios já, mais e ainda nas orações negativas (Revista de Estudos da Linguagem, 1993)
This paper follows a functional approach which takes into account the real use of language as an instrument of communication. We are malnly lnterested ln lnvestigating the ways through whlch syntax, semantics and pragmatics interact. ln order to do this, we study the behaviour of the adverbs já, mais and ainda ln negative sentences. First, we review the use of some elements which reinforce the very idea of negation. Secondly, we deal, specifically, with the adverbs, já, mais and ainda as a reinforcement to the negative. Thirdly, we aim at verifying their behaviour from an argumentative perspective. Finally, we present our conclusions.